Ginaton reduces M1-polarized macrophages in hypertensive cardiac remodeling via NF-κB signaling - Wang, Jie; Cai, Enze; An, Xiangbo; Wang, Junjie (Frontiers in Pharmacology, 2023)
Macrophages play a critical role in cardiac remodeling, and dysregulated macrophage polarization between the proinflammatory M1 and anti-inflammatory M2 phenotypes promotes excessive inflammation and cardiac damage. Ginaton is a natural extract extracted from Ginkgo biloba. Because of its anti-inflammatory properties, it has long been used to treat a variety of diseases. However, the role of Ginaton in modulating the diverse macrophage functional phenotypes brought on by Ang II-induced hypertension and cardiac remodeling is unknown. Given this, in the present study, we fed C57BL/6J mice in the age of eight weeks with Ginaton (300 mg/kg/day) or PBS control, and then injected Ang II (1000 ng/kg/min) or saline for 14 days to investigate the specific efficacy of Ginaton. Systolic blood pressure was recorded, cardiac function was detected by echocardiography, and pathological changes in cardiac tissue were assessed by histological staining. Different functional phenotypes of the macrophages were assessed by immunostaining. The mRNA expression of genes was assessed by qPCR analysis. Protein levels were detected by immunoblotting. Our results showed that Ang II infusion significantly enhanced the activation and infiltration of macrophages with hypertension, cardiac insufficiency, myocardial hypertrophy, fibrosis and M1 phenotype macrophages compared with the saline group. Instead, Ginaton attenuated these effects. In addition, in vitro experiments showed that Ginaton inhibited Ang II-induced activation, adhesion and migration of M1 phenotype macrophages. Most importantly, Ginaton will be an effective drug for the treatment of hypertensive cardiac remodeling in the future.